A corrugated-core sandwich beam with local resonators for low-frequency broadband elastic wave attenuation. (December 2022) - Xi, Chenyang; Zhu, Xiaosong; Zheng, Hui
This article attempts to enhance the low-frequency vibration suppression performance of corrugated-core sandwich beams. Multiple local resonators are introduced into the corrugated-core sandwich beam to acquire low-frequency bandgaps with broader bandwidth and higher wave attenuation capability. The governing equations for vibration analysis of the local resonator–attached corrugated-core sandwich beam are established based on the spectral element method, which incorporates the locally resonant effect by adding the dynamic stiffness term of one specific resonator to the degree of freedom that it attaches to. The bandgaps of the proposed periodic structure are further derived by imposing the Bloch boundary conditions. After validating the numerical model through finite element simulations as well as experimental investigations, the bandgaps and vibration transmissibility of the corrugated-core sandwich beam are carried out, both with and without attached local resonators. It is found that the vibration reduction capability of the corrugated-core sandwich beam is greatly enhanced, bringing two low-frequency bandgaps with high attenuation factors and wide bandwidths. Meantime, the first bandgap of resonator-free corrugated-core sandwich beam is broadened apparently. An interesting result is that the bandgap with higher frequency is split by a newly generated passband. Furthermore, parametric studies are performed, and it is found that the regulating characteristics of the bandgaps obtained through varying the attachment location of local resonators are similar to those through tuning their inherent parameters.